To what degree and how do healthcare professionals in nursing homes and homecare practice user involvement? A mixed methods study - Eline Ree; Siri Wiig; Jeffrey Braithwaite; Ingunn Aase (Scandinavian University Press (Universitetsforlaget), 2020)
Background: Involving patients and users may contribute to sound quality and safety in healthcare services. We examined the degree to which and how user involvement is practiced in daily work and in quality improvement in nursing homes and homecare. Methods: Mixed methods design. Focus groups and individual interviews with managers (n=45), and employees (n= 40) from 15 Norwegian care settings were conducted. Data were analyzed via systematic text condensation. Survey data from four homecare services (N=139) and four nursing homes (N=165) were analyzed using descriptive statistics and t-tests. Results: Participants focused on supporting independence in users and involved them in activities that increased coping. Knowing users was an important prerequisite. Challenges related to poor communication leading to several cross-pressures between users, relatives and healthcare professionals. There were no differences between nursing homes and homecare on the degree of user involvement in daily work and in quality improvement; both scored significantly lower on the latter. Conclusion: User involvement is an important part of the daily work of healthcare professionals in care settings. Participants seemed to lack knowledge on how to use patients' experience to inform quality improvement. A key remedial strategy is training healthcare professionals in involving users in quality improvement.